Properties of Hg 1-xCd xTe epitaxial films grown on (211)CdTe and (211)CdZnTe - Di Stefano, María Cristina (2004)
Hg 1-xCd xTe (MCT) epitaxial films have been grown employing single crystalline substrates of CdTe and Cd 0.96Zn 0.04Te with (211)Cd and (211)Te crystalline orientations. The Isothermal Vapor Phase Epitaxy (ISOVPE) technique without Hg overpressure has been used for the epitaxial growth. Substrates and films were characterized by optical microscopy, chemical etching and x ray diffraction (Laue technique). The electrical properties were determined by Hall effect measurements. The characterization results allowed to evaluate the crystalline quality of MCT films.